An Evaluation of the Current Status of Agricultural Implements Manufacturing Industries: Emission of Pollutants Perspective (International Journal of Innovative Research in Computer Science & Technology, 2021)
Agricultural Implements manufacturing  industries use raw material from the Iron and steel industry  to produces agricultural machinery products. If we explore  the research done in past, a majority of work has been taken  on iron and steel industry regarding the environment. These  industries are adversely affecting the environment in  manufacturing process. This research has tried to add the link  that the agricultural manufacturing industry is taking the raw  material from iron and steel industry while the iron and steel  industry is affecting the environment in the process of  production. For this reason research has also analyzed the  relevant reference (objective wise) of manufacturing  industries industry in paper. On the basis Literature survey  identified the research gap and this research paper proposed  the current scenario of agricultural implements  manufacturing. An evaluation of the current status of  Agricultural Implements manufacturing industries w.r.t their emission of pollutants and their level of significance have  been analyzed including EMP plan for industries and  government.
Keywords: Manufacturing Industries; Environment; Pollution; Emission of Pollutants; Emission and Effusion